The Effect of Land Use Change on Flood Discharge in Batam City Using GIS Analysis - Sri Dewi Lestari; Ade Jaya Saputra; Joewono Prasetijo (Journal of Civil Engineering and Planning (JCEP), 2025)
This study aims to analyze the effect of land use change on flood discharge in Batam City for the period 2014–2023 by integrating spatial analysis based on Geographic Information System (GIS) and hydrological analysis using the Rational Method. The data used included Landsat satellite images from 2014 and 2023, annual maximum rainfall data for 10 years, and data on the area of the river basin. Land use changes were analyzed through supervised classification and their contribution to changes in the runoff coefficient was calculated based on the area of each land class. The results of the study show a 10.86% reduction in forest area and a 4.50% increase in built-up land. These changes have resulted in an increase in the average runoff coefficient of the watershed, which in turn has increased the maximum planned flood discharge. The calculation results show an increase in average flood discharge of 11.89% or around 50.47 m³/second from 2014 to 2023. This study confirms that land use changes due to urbanization contribute significantly to an increased risk of flooding in Batam City, thus requiring sustainable spatial management.